A Clinical Case of Aplastic Anemia After COVID-19 Infection - G. Sh. Safuanova; А. С. Константинова; A. A. Latypova; A. U. Bagautdinova; D. R. Safuanova (Архивъ внутренней медицины)
Aplastic anemia is a rare disease of the blood system characterized by suppression of hematopoiesis in all lines of hematopoiesis, replacement of hematopoietic tissue with fatty tissue and absence of other causes or diseases that can suppress hematopoiesis. The incidence is 2-3 cases per 1 million population per year in the regions of Europe and America, rates are 2-3 times higher in East Asia. The disease most often begins between the ages of 10 and 25 years and over 60 years. The etiology remains unknown in 70-80 % of cases. The frequency of acquired cases predominates over congenital cases. The triggering factors can be chemical, physical exposures, medications, and viral infections. This case report describes a case of a patient developing aplastic anemia, as a result of a coronavirus infection.